Challenges and limitations of introducing pigeonpea as a new crop into smallholder farming systems through farmer‐to‐farmer education in Zambia - Khazaei, Hamid; Scott, Sebastian; Niemi, Jarkko K. (John Wiley & Sons, 2026)
Societal Impact Statement Legume plants offer generous benefits for both the planet and people by supporting sustainable farming, food and feed systems through their ability to symbiotically fix atmospheric nitrogen. While grain legumes are cultivated and consumed globally, their adoption, market development, and integration into cropping systems vary. In Zambia, pigeonpea remains an underutilised legume crop despite its suitability for semiarid conditions and potential to diversify food and income sources. We implemented farmer field schools in the Eastern province of Zambia to introduce pigeonpea, strengthen farmer knowledge, and explore how participatory learning can support its adoption and early-stage value chain development. Summary Farmer field schools (FFSs) are transformative, participatory approaches to adult agricultural education that effectively promote farmers' learning and capacity building and empower farming communities with practical knowledge. Here, we present a case study of FFSs in the Katete district, Eastern province of Zambia, focused on good pigeonpea agronomic practices and the value chain. Three FFSs were established, focusing on pigeonpea variety trials, biological pesticides, and a pigeonpea-specific rhizobial inoculant development and testing. Farmers received hands-on training and resources and were guided through community-led trials. Extreme weather conditions, free-grazing livestock, an underdeveloped pigeonpea seed value chain, and a poor seed system hindered the implementation of the FFSs. Despite the challenges encountered, we successfully designed and tested pigeonpea-specific rhizobial inoculants, trained farmers in good agronomic practices such as biological pest control, and provided access to seed of improved pigeonpea varieties. To strengthen the pigeonpea seed value chain, a seed dehuller is now available to farmers. Pigeonpea FFSs will support crop and food diversification, improve soil fertility and sustainable agriculture, and may increase household income.
Keywords: Africa; farmer education; grain legumes; rhizobial inoculation; seed processing